ANALISIS KUALITAS LAYANAN PAJAK KENDARAAN BERMOTOR (PKB) DENGAN MODEL DRIVE THRU DI KANTOR BERSAMA SAMSAT MANYAR SURABAYA - Widajantie, Tituk Diah; Suhartini, Dwi (Journal of Accounting and Strategic Finance, 2010)
Quality utilize to gratify the Taxpayer and lessen each, every existence of sigh from service that  accepted by taxpayer, hence one of effort which is gone through by execution of service of Samsat Drive Thru. The conception of this service Drive Thru is service being based on Information Technology ( IT) where all of these online system to the mains computer so that its process do not take much time and more effective. Pursuant to the background, hence this research target is to prove that tangible, reliability, responsiveness, assurance, empathy and efficiency of of Drive Thru system have an effect on to motivation of compliance of Taxpayer in Samsat Manyar Surabaya.Taxpayer with one object in the last year 2008 as much more or less 311.169 of taxpayer, hence to the number of sample used as much 400 Motor Vehicle Taxpayer, with the method of Simple Random Sampling. Pursuant to result analyze the multiple linear regression and studying we have some conclusion that is dimension or element of service quality covering variable tangible, reliability, responsiveness, assurance, empathy and efficiency of Drive Thru model by which entirely and partial have an effect on to motivation of compliance of taxpayer of motor vehicle in Samsat Manyar Surabaya office. Keywords : Tangible, Reliability, Responsiveness, Assurance, Empathy, Efficiency, Motivate The Compliance